Penerapan Digital Marketing pada E-commerce dan Media Sosial dalam Upaya Peningkatan Penjualan Knalpot Alpino Exhaust di Shopee - Eliya Agustin Eka Putri; Rahadyan Tajuddien (STIE Bina Karya, 2026)
The development of information technology has significantly transformed marketing strategies. Companies are now required to adapt through the implementation of digital marketing that utilizes e-commerce and social media platforms. This study aims to analyze the role of digital marketing in e-commerce and social media in increasing the sales of Alpino Exhaust products on Shopee. The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The results show that the application of digital marketing through Shopee and social media such as Instagram and TikTok plays an important role in increasing consumer interest, expanding market reach, and strengthening brand image. Consistent digital promotion strategies have proven effective in increasing sales and enhancing Alpino Exhaust’s competitiveness in the national automotive market.